2022
DOI: 10.3390/jcm11113230
|View full text |Cite
|
Sign up to set email alerts
|

Will Coiling Survive through the Next Decade?

Abstract: During the past three decades, neuroendovascular therapy has evolved from a focus on new disease concepts to revised treatment strategies and, ultimately, to versatile new technologies [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In this study we present the second largest case series on NICE lesions to date and the largest series specifically regarding flow diversion, which is of particular interest as FDs are increasingly used to treat various aneurysms and their use will likely further increase in the future. 21 For example, Cruz et al reported in their case series on two of seven patients treated with FDs, 22 three of six patients were treated with FDs in the series by Bayas et al, 4 and six of 32 patients were treated with FDs in the largest case series to date by Shotar et al 2 Biopsy-confirmed cases have shown that NICE lesions result from granulomatous foreign body reactions to microemboli formed by hydrophilic polymer coatings. The biopsies unveiled a spectrum of pathological findings including granulomas, angiitis, a periadventitial response characterized by giant cells reacting to foreign bodies, and microabscesses encapsulating foreign material, along with neutrophilic granulocytes and multinucleated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we present the second largest case series on NICE lesions to date and the largest series specifically regarding flow diversion, which is of particular interest as FDs are increasingly used to treat various aneurysms and their use will likely further increase in the future. 21 For example, Cruz et al reported in their case series on two of seven patients treated with FDs, 22 three of six patients were treated with FDs in the series by Bayas et al, 4 and six of 32 patients were treated with FDs in the largest case series to date by Shotar et al 2 Biopsy-confirmed cases have shown that NICE lesions result from granulomatous foreign body reactions to microemboli formed by hydrophilic polymer coatings. The biopsies unveiled a spectrum of pathological findings including granulomas, angiitis, a periadventitial response characterized by giant cells reacting to foreign bodies, and microabscesses encapsulating foreign material, along with neutrophilic granulocytes and multinucleated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Our institution is a tertiary referral center with an average of 1224 neurovascular interventions per year in the period of 2015–2021, including an average of 162 coiling procedures, 212 procedures with implantation of one or more flow-diversion units [ 21 ], an average of 376 thrombectomies and 212 primary carotid interventions per year. The catheter laboratory team consists of 6 interventionalists including 3 senior interventionalists.…”
Section: Methodsmentioning
confidence: 99%